Generic skills: Attending to the communication skills needs of international students - Briguglio, Carmela (Lifelong Learning Conference Committee, 2000)
Of all the generic skills and attributes considered necessary for lifelong learning, communication skills are perhaps the most critical. This paper discusses issues of educational support required by Non English-Speaking Background (NESB)/international students to enable them to become more proficient in English language communication, and offers some suggestions based on the findings of several research projects undertaken at Curtin University of Technology.